2022
DOI: 10.3389/fpsyg.2022.911177
|View full text |Cite
|
Sign up to set email alerts
|

Explanations and Causal Judgments Are Differentially Sensitive to Covariation and Mechanism Information

Abstract: Are causal explanations (e.g., “she switched careers because of the COVID pandemic”) treated differently from the corresponding claims that one factor caused another (e.g., “the COVID pandemic caused her to switch careers”)? We examined whether explanatory and causal claims diverge in their responsiveness to two different types of information: covariation strength and mechanism information. We report five experiments with 1,730 participants total, showing that compared to judgments of causal strength, explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Such explanations seem more satisfying compared to ones that identify factors thought to be associated with the outcome and shown capable of producing it but without explaining the mechanism involved (Zemla et al 2017(Zemla et al 2022. Mechanistic explanations are thought to be preferred because they provide a sense of understanding (Vasilyeva and Lombrozo 2015;Rozenblit and Keil 2002) whether or not the explanation is correct (Ahn et al 1995). 'This is how it could happen' overrides evidence that this is what does happen (Kuhn 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such explanations seem more satisfying compared to ones that identify factors thought to be associated with the outcome and shown capable of producing it but without explaining the mechanism involved (Zemla et al 2017(Zemla et al 2022. Mechanistic explanations are thought to be preferred because they provide a sense of understanding (Vasilyeva and Lombrozo 2015;Rozenblit and Keil 2002) whether or not the explanation is correct (Ahn et al 1995). 'This is how it could happen' overrides evidence that this is what does happen (Kuhn 1991).…”
Section: Introductionmentioning
confidence: 99%
“…'This is how it could happen' overrides evidence that this is what does happen (Kuhn 1991). Both empirical evidence and mechanistic explanation have justifiable roles to play in explaining events, and it is less than straightforward to prescriptively judge their relative roles (Ahn et al 1995;Koslowski 1996;Walker et al 2017;Vasilyeva and Lombrozo 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many factors have been shown to affect how we judge explanations, we ask whether preferences change depending on whether or not an explanation describes causal mechanisms. While some studies have directly compared explanations with and without mechanisms (e.g., Ahn & Bailenson, 1996;Vasilyeva & Lombrozo, 2015), most have not. Here, we test whether explanations that describe mechanisms are evaluated differently than explanations that do not contain mechanisms, with a focus on one explanatory virtue: simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Keil (2017) found this to be especially common when evaluating token claims (e.g., smoking caused John's lung cancer) compared to type claims (e.g., smoking causes cancer). Vasilyeva and Lombrozo (2015) found that explanations with mechanisms are typically judged as better than their counterparts without mechanisms. In the same study, participants rated their subjective understanding of a phenomenon as higher when the explanations contained mechanisms.…”
mentioning
confidence: 99%